Molecular characterisation of the lateral organ boundaries gene (XvLOB) from the resurrection plant Xerophyta viscosa - Sattar, Shakiera (Department of Molecular and Cell Biology, 2015)
The aim of this study is to preliminary characterise XvLOB, a LOB domain containing gene, which has been isolated from a dehydration stress library in X. viscosa. In this study the gene was isolated and cloned, the DNA and amino acid sequences were analysed by in silico analysis, the recombinant XvLOB protein expressed, subcellular localisation examined and both the transcript and protein expression levels in response to dehydration was investigated.